Social Distancing, Vaccination and Evolution of Covid-19 Transmission Rates in Europe - Alexander Chudik; M. Hashem Pesaran; Alessandro Rebucci (Center for Economic Studies and ifo Institute (CESifo), 2022)
This paper provides estimates of COVID-19 effective reproduction numbers and explains their evolution for selected European countries since the start of the pandemic taking account of changes in voluntary and government mandated social distancing, incentives to comply, vaccination and the emergence of new variants. Evidence based on panel data modeling indicates that the diversity of outcomes that we document may have resulted from the non-linear interaction of mandated and voluntary social distancing and the economic incentives that governments provided to support isolation. The importance of these factors declined over time, with vaccine uptake driving heterogeneity in country experiences in 2021. Our approach, also allows us to identify the basic reproduction number, R0. It is precisely estimated and differ little across countries.
Keywords: D00; F60; C40; I12; E70; 330; COVID-19; multiplication factor; under-reporting; social distancing; self-isolation; SIR model; reproduction number; pandemics; vaccine